Arsitektur Convolutional Neural Network Ringan Untuk Pengenalan Ekspresi Wajah: Lightweight Convolutional Neural Network Architecture For Facial Expression Recognition - Robot, Reynold; Karenia Lolowang, Miesje; Dwisnanto Putro, Muhamad (Universitas Sam Ratulangi, 2024)
Abstract — Facial expression recognition presents the challenge of applicability to real scenarios which demands to involve lightweight algorithms to operate at real-time speed. The proposed work offers a lightweight convolutional neural network architecture to accurately predict facial expressions. It considers the use of parameters and computations that are not massive. thus applying lightweight convolution operations. A channel compression technique at the center is applied to reduce parameter usage and redundant operations. Testing the accuracy results was conducted on the KDEF dataset. This dataset is a knowledge source that provides information on seven facial expressions with varying poses. Augmentation techniques were used to increase the variety and training configuration strategies were applied to optimize the network training work. As a result, the proposed model achieves an accuracy of 0.9732 which outperforms competing CNN architectures. Besides, it also produces a lightweight parameter of 2.8 M which can encourage the model to operate fast on Jetson Nano devices. The proposed architecture produces an effective deep learning model for predicting facial expressions from a chunk of input image without compromising its efficiency. Key words— convolutional neural network; Facial expressions; lightweight architecture; model efficiency. Abstrak — Pengenalan ekspresi wajah menghadirkan tantangan penerapan pada skenario nyata yang menuntut untuk melibatkan algoritma yang ringan agar dapat beroperasi dengan kecepatan waktu nyata. Pekerjaan yang diusulkan menawarkan sebuah arsitektur convolutional neural network yang ringan untuk memprediksi ekspresi wajah secara akurat. Ini mempertimbangan penggunaan parameter dan komputasi yang tidak massif sehingga menerapkan operasi konvolusi yang ringan. Teknik pemampatan kanal pada bagian tengah diterapkan untuk mengurangi penggunaan parameter dan operasi berlebihan. Pengujian hasil akurasi diadakan pada dataset KDEF. Dataset ini merupakan sumber pengetahuan yang menyediakan informasi tujuh ekspresi wajah dengan pose yang bervariasi. Teknik augmentasi digunakan untuk memperbanyak variasi dan strategi konfigurasi pelatihan diterapkan untuk mengoptimalkan pekerjaan pelatihan jaringan. Sebagai hasil, model yang diusulkan meraih akurasi sebesar 0.9732 yang mengungguli arsitektur CNN pesaing. Disamping itu, ini juga menghasilkan parameter yang ringan sebesar 2.8 M yang dapat mendorong model untuk beroperasi cepat pada perangkat Jetson Nano. Arsitektur yang diusulkan menghasilkan model pembelajaran mendalam yang efektif untuk memprediksi ekspresi wajah dari sebuah potongan masukan citra tanpa mengabaikan efisiensinya. Kata kunci — Arsitektur ringan; convolutional neural network; efisiensi model ; ekspresi wajah